A COMPARATIVE STUDY OF LATERAL INTERNAL SPHINCTEROTOMY VERSUS FISSURECTOMY IN THE TREATMENT OF CHRONIC ANAL FISSURE - Dr. Mahadeo R Patil, Dr. Sandhyarani M Patil, Dr Abhijit R Patil, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
An anal fissure is linear tear extending from mucocutaneous junction to thedentate line which is a very common problem in general population. Anal fissures are eitheracute or chronic. Chronic fissures not responding to conservative treatment typically requiresurgical treatment. The surgical options include lateral internal sphincterotomy (LIS) andfissurectomy. The aim of the study is to compare lateral internal sphincterotomy andfissurectomy in terms of postoperative pain relief, healing of fissure, and postoperativecomplications.